A life-threatening duodenal ulcer hemorrhage due to previously unknown primary hyperparathyroidism. (10th September 2016) - Xie, Dan; Hu, Kunpeng; Xian, Ying; Wang, Ying; Yuan, Xiaofeng; Li, Mingliang; Bi, Xiaogang; Zhang, Kouxing
Abstract: Peptic ulcer bleeding due to primary hyperparathyroidism is extremely rare. We report a case of a 42-year-old male with life-threatening acute upper gastrointestinal bleeding secondary to a duodenal ulcer and a history of kidney stones. Gastroscopic therapy, Billroth II gastrointestinal anastomosis and angiographic embolization were sequentially conducted to arrest the hemorrhage. A complete investigative work-up revealed that the duodenal ulcer bleeding was due to primary hyperparathyroidism coexisting with a parathyroid adenoma. Following this event, the patient developed a severe abdominal cavity infection and sepsis. An elective parathyroidectomy was performed, and the histology was confirmed to be a typical parathyroid adenoma. Postoperatively, the patient's calcium and parathyroid levels were normalized. Attention should be paid to patients with an upper gastrointestinal ulcer, especially when it is accompanied by kidney stones.